2017
DOI: 10.1111/jsr.12583
|View full text |Cite
|
Sign up to set email alerts
|

Integrative body–mind–spirit intervention for concurrent sleep and mood disturbances: sleep‐specific daytime functioning mediates sleep and mood improvements

Abstract: Summary Sleep disturbances and depressive symptoms are associated closely with daytime dysfunctions, yet few studies have investigated their temporal relationship in a randomized controlled trial. We investigated the inter‐relationships among sleep, depressive symptoms and daytime functioning following an integrative body–mind–spirit (I‐BMS) intervention. One hundred and eighty‐five participants (mean age 55.28 years, 75.1% female) with co‐existing sleep and depressive symptoms were randomized to I‐BMS or wait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Being more grounded, people may broaden their awareness and build a connection with the mind and spirit. Brief BMS practices have been evaluated and assessed with plenty of evidences in a wide range of clients, for instance, people with mood and sleep disturbances, chronic fatigue, and survivors of critical incidents ( Ng et al, 2006 ; Chan et al, 2016 , 2017 ; Ji et al, 2017 ). Given the emotional demanding nature of social services, we developed a brief daily BMS program and successfully piloted it with both professional and care workers at elderly service ( Ng, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Being more grounded, people may broaden their awareness and build a connection with the mind and spirit. Brief BMS practices have been evaluated and assessed with plenty of evidences in a wide range of clients, for instance, people with mood and sleep disturbances, chronic fatigue, and survivors of critical incidents ( Ng et al, 2006 ; Chan et al, 2016 , 2017 ; Ji et al, 2017 ). Given the emotional demanding nature of social services, we developed a brief daily BMS program and successfully piloted it with both professional and care workers at elderly service ( Ng, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The patient's negative emotions were eliminated, self‐confidence was fully restored, and she resumed college life. According to the principle of integrative body–mind–spirit [15], the patient's holistic health has been achieved, and the dual goals of clinical and psychological healing were established, which was our original goal.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Huang, it was detected that depressed mothers in the early postpartum period showed more daytime dysfunction than non-depressive mothers 43 . In the study conducted by Ji, Daytime dysfunction was found to be related with changes in depressive symptoms rather than changes in nighttime sleep in patients with comorbid major depression and primary sleep disorder 44 . In a study conducted in the geriatric age group, it was found that geriatric depression scale scores were perfectly associated with daytime dysfunction 45 .…”
Section: Discussionmentioning
confidence: 95%